Father's Attitudes About Breastfeeding Practices In Batam City: A Learning Practice Model - Prasida Yunita, Mohamed Saifulaman, Musheer AlJaberi (South Eastern European Journal of Public Health, 2025)
The success of exclusive breastfeeding is intrinsically linked to family support and involvement, including parents, in-laws, and particularly the husband's support as the closest individual in maintaining the mother's motivation to breastfeed until the infant reaches six months of age. Paternal involvement in supporting breastfeeding practices has emerged as one of the most significant factors influencing breastfeeding outcomes. This study aimed to evaluate the effectiveness of educational interventions on fathers' attitudes in supporting breastfeeding practices. The research employed a quantitative approach and a True Experimental Design utilizing the Solomon Four-Group Design, which comprised four groups: two groups underwent pre-testing, two groups received treatment, and all groups participated in post-testing. The study population consisted of fathers-to-be whose partners were in their third trimester of pregnancy, involving 164 participants who were divided into four groups based on intervention exposure. The results demonstrated a significant increase in supportive attitudes in the experimental group compared to the control group (p < 0.005). Educational interventions proved effective in enhancing fathers' understanding and positive attitudes toward exclusive breastfeeding. This study suggests implementing interventions from early pregnancy for optimal outcomes.